Decay of Temperature Fluctuations in MHD Turbulent flow in presence of dust particles before the final period - Rahman, ML (Journal of Bangladesh Academy of Sciences, 2009)
This paper reports the decay of temperature fluctuation in homogeneous MHD turbulence in the presence of dust particles before the final period. We have considered the two and three point correlation equations and solved them after neglecting the fourth order correlations in comparison with the second and third order correlations. Finally, the energy decay law for temperature fluctuation of MHD turbulence in the presence of dust particles at times before the final period is obtained. doi: 10.3329/jbas.v32i1.2443 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 61-70, 2008